Baseballism : is Japan a good play? - Biseda, Marlene A.; Shanahan, Doreen E. (London : Pepperdine University, Graziadio School of Business and Management, 2019)
Four young entrepreneurs set out on a journey to channel their love of the game of baseball into a means for earning some income while attending college. The baseball camp they started in college eventually pivoted into a premium line of "off the field baseball apparel and accessories." The business was rapidly growing and the four founders were looking to continue to fuel the momentum for the brand. The company's founders believed that Japan, whose population has a strong affinity for baseball, could be an attractive market for the company to enter. Baseballism, however, was a small growing company with limited resources - both human capital and money. The executives realized that a misstep at this stage of their business could have a devastating impact on the company. As they contemplated expanding into foreign markets, they questioned if Japan was a potential market for Baseballism.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Baseballism -- Management; New business enterprises -- Case Studies; International business enterprises -- Case studies; Sport clothes industry -- Japan -- Case studies; Baseball fans -- Japan